The relationship between sport types, sex and visual attention as assessed in a multiple object tracking task - Jin, Peng; Zhao, Zi-Qi; Zhu, Xiao-Feng (Frontiers in Psychology, 2023)
This study was conducted to examine differences in visual attention according to sports type and sex. In total, 132 participants [open-skill sport athletes (basketball players), closed-skill sport athletes (swimmers), and non-athletes; n = 22 men and 22 women each] aged 19–24 years performed a multiple object tracking (MOT) task, which is a well-established paradigm for the assessment of visual attention. Visual tracking accuracy was affected by the sport type (p < 0.001), being superior among basketball players than among swimmers and non-athletes, with no significant difference between the latter groups. It also varied by sex (p < 0.001), being superior among males than among females. Significant interaction between the sport type and sex was observed (p < 0.001), with male and female basketball players showing similar tracking accuracy. Our results demonstrate that open-skill sport activities strongly related to visual attention, as estimated by MOT task performance, and that sex plays a role in this performance. They also indicate that females might gain a greater visual attention advantage from open than from closed-skill sports participation, as long-term open-skill sports training appeared to minimize the sex difference in visual attention.